ANALISIS KEBERHASILAN REDENOMINASI MATA UANG: STUDI KASUS DI 31 NEGARA YANG TELAH MELAKSANAKAN REDENOMINASI - Lella Nurlela Qushoy; Intan Ramdaniatulfitri; Dara Kusumah (Jurnal Riset Ilmu Ekonomi, 2021)
There are so many countries in the world that are trying to maintain their economic stability. This is partially done in order to achieve a number of economic goals in their respective countries. One of the many realized efforts was currency redenomination. However, as the policy rolled around, it turned out that not all countries succeeded in obtaining the output as expected. Therefore, this research is intended to reveal what success factors are necessary to implement in an effort to implement the currency redenomination policy. Furthermore, the research was carried out using quantitative methods and secondary data which were further analyzed using logistic regression analysis. The data obtained were sourced from the World Bank, the International Monetary Fund, The Center for Systemic Peace, and the United Nations Development Program. This research also immediately succeeded in revealing that of the many variables and data elements that were processed, only the variables of economic growth, unemployment, and the human development index turned out to show significant progress towards the success of the redenomination. Meanwhile, interest rates also had a positive effect on the success of the redenomination, although not significantly.